Environmental Friendly Scalable Production of Colloidal 2D Titanium Carbonitride MXene with Minimized Nanosheets Restacking for Excellent Cycle Life Lithium-Ion Batteries. (1st May 2017) - Du, Fei; Tang, Huan; Pan, Limei; Zhang, Tian; Lu, Hanmei; Xiong, Jie; Yang, Jian; Zhang, Chuanfang (John)
Graphical abstract: Highlights: Colloidal Ti3 CNTx MXene was prepared in the absence of HF or organics intercalation. The restacking of delaminated Ti3 CNTx flakes was greatly suppressed by freeze-drying. The freeze-dried Ti3 CNTx shows developed ion diffusion paths with abundant voids. The capacity of freeze-dried Ti3 CNTx reaches 300 mAh/g at 0.5 A/g after 1000 cycles. The delamination/freeze-drying process for MXene is facile, scalable, and general. Abstract: Developing powerful Li-ion batteries require advanced nanostructured electrodes. Transition metal carbides or nitrides, known as MXenes, are an emerging family of two-dimensional materials. However, the lacking of an environmental-friendly preparation of colloidal MXene with few nanosheets-restacking greatly limits their usage in batteries and compromises the electrochemical performances. Here, we obtained the aqueous titanium carbonitride (Ti3 CNTx ) colloidal solution in the absence of hydrofluoric acid or organic solvents' intercalation processes. We further suppressed the notorious nanosheets restacking issue through a freeze-drying strategy of the colloidal dispersion. The resulted Ti3 CNTx powder, with a "fluffy" morphology and quite few percentage of restacked nanosheets, displays good charge storage capacities, high rate handling and excellent cycling performance, for example, a discharge capacity of 300 mAh g −1 at 0.5 A g −1 after 1000 cycles has been achieved.